Pengaruh Persepsi Konsumen Terhadap Keputusan Penggunaan Aplikasi Grab Pasca New Normal (Khususnya Layanan Transportasi) Di Kota Palembang - Satiti Pangestu (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of consumer perceptions on the decision to use the postnew normal Grab application (especially transportation services) in the city of Palembang. This study took samples using a non-probability sampling technique using purposive sampling. Nonprobability sampling is a sampling technique that does not provide equal opportunities for each member of the population to be selected as a sample. The results of the research based on regression calculations and hypothesis testing show that consumer perceptions have a positive and significant effect on the decision to use the post-new normal Grab application (especially transportation services) in the city of Palembang, as well as the decision to use the post-new normal Grab application (especially transportation services) in the city of Palembang. Palembang is more dominated by the influence of indicators because it is equipped with Grab protect, namely plastic partitions to protect drivers and passengers.